2008
DOI: 10.1016/j.ejcts.2008.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Preserving and evaluating hearts with ex vivo machine perfusion: an avenue to improve early graft performance and expand the donor pool☆

Abstract: Cardiac transplantation remains the first choice for the surgical treatment of end stage heart failure. An inadequate supply of donor grafts that meet existing criteria has limited the application of this therapy to suitable candidates and increased interest in extended criteria donors. Although cold storage (CS) is a time-tested method for the preservation of hearts during the ex vivo transport interval, its disadvantages are highlighted in hearts from the extended criteria donor. In contrast, transport of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 57 publications
(75 reference statements)
0
53
0
2
Order By: Relevance
“…One of the main reported disadvantages in the animal studies is the association of MP with increased myocardial edema, 115 with some studies showing a variation depending on the preservation solution. [116][117][118][119] This association is thought to be mediated by MPdependent hydrostatic pressure and perfusate colloid oncotic pressure and further compounded by the lack of lymphatic flow to the arrested heart. 118 Collins and associates suggested that lack of physiological variation in coronary artery flow and pressures also may contribute to edema formation, 118 which is thought to be associated with impaired posttransplant diastolic function recovery.…”
Section: Limitations Of Machine Perfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main reported disadvantages in the animal studies is the association of MP with increased myocardial edema, 115 with some studies showing a variation depending on the preservation solution. [116][117][118][119] This association is thought to be mediated by MPdependent hydrostatic pressure and perfusate colloid oncotic pressure and further compounded by the lack of lymphatic flow to the arrested heart. 118 Collins and associates suggested that lack of physiological variation in coronary artery flow and pressures also may contribute to edema formation, 118 which is thought to be associated with impaired posttransplant diastolic function recovery.…”
Section: Limitations Of Machine Perfusionmentioning
confidence: 99%
“…[116][117][118][119] This association is thought to be mediated by MPdependent hydrostatic pressure and perfusate colloid oncotic pressure and further compounded by the lack of lymphatic flow to the arrested heart. 118 Collins and associates suggested that lack of physiological variation in coronary artery flow and pressures also may contribute to edema formation, 118 which is thought to be associated with impaired posttransplant diastolic function recovery. 115 More recently, Ozeki and associates suggested that increased edema may only be transient.…”
Section: Limitations Of Machine Perfusionmentioning
confidence: 99%
“…Continuous machine perfusion of donor hearts has been proposed as an alternative and superior method of donor heart preservation compared to cold static storage [16]. Continuous ex vivo heart perfusion demonstrated a beneficial influence on aerobic metabolism during the preservation of the donor heart by maintaining cell integrity and vital cell function [17].…”
Section: Ex Vivo Pretransplant Organ Reconditioningmentioning
confidence: 99%
“…Collins et al [6,20] reported cases in which hearts were successfully resuscitated by hypothermic machine perfusion with full recovery of function. They could also resuscitate one of the two hearts which belonged to Non Beating Heart Donors (NBHDs).…”
Section: Review On Experimental Researchmentioning
confidence: 99%
“…The above zones were implemented to facilitate transplant coordination and to minimize ischemic time [6]. More information about prioritized match candidates based on the level of urgency for transplantation can be found in OPTN policies [4].…”
Section: Introductionmentioning
confidence: 99%